1999
DOI: 10.1038/sj.bjp.0702736
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated effects on splanchnic homeostasis by selective and non‐selective endothelin receptor antagonism in porcine endotoxaemia

Abstract: 1 The non-selective endothelin (ET) receptor antagonist bosentan has been shown to restore systemic and gut oxygen delivery and reverse intestinal mucosal acidosis in porcine endotoxin shock. 2 To further elucidate the speci®c role of the ET A as opposed to the ET B receptor and their e ects in the splanchnic region a non-selective (ET MIX ra) A-182086 and selective ET A (ET A ra) PD155080 and ET B (ET B ra) A-192621 receptor antagonists were administered, separately or simultaneously (ET A+B ra) 2 h after ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
4
11
0
Order By: Relevance
“…In healthy humans, ET A receptor agonism seems to provide enhanced myocardial contractile function, which does not occur in patients with dilated cardiomyopathy (23). Previous results from our own laboratory in which selective ET B receptor antagonism in septic pigs was used proved to be fatal, whereas dual ET receptor antagonism seems beneficial (20,28). The mechanisms behind these apparent diverging results are not fully elucidated.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In healthy humans, ET A receptor agonism seems to provide enhanced myocardial contractile function, which does not occur in patients with dilated cardiomyopathy (23). Previous results from our own laboratory in which selective ET B receptor antagonism in septic pigs was used proved to be fatal, whereas dual ET receptor antagonism seems beneficial (20,28). The mechanisms behind these apparent diverging results are not fully elucidated.…”
mentioning
confidence: 64%
“…Changes in receptor density as well as alterations in ET A -to-ET B receptor ratio may be involved (2). Furthermore, the cardiac unloading effects from vasodilation may result in overall beneficial hemodynamic responses, masking the potential negative inotropic effects seen in response to ET receptor antagonism in various conditions, such as sepsis (28).…”
mentioning
confidence: 99%
“…Endothelin peptides act via two distinct receptors, namely ET A and ET B [31], and a cross-talk between the endothelin receptors has also been reported to contribute in various pathological conditions [32]. For example, it was shown that ET B receptor sensitivity increases during endothelin ET A receptor antagonism [32] and this phenomenon results in an increase in afterload and cardiovascular collapse in septic shock [33].…”
Section: Discussionmentioning
confidence: 97%
“…As the most potent vasoconstrictor agent ever found, the endothelin peptides produce splanchnic ischemia [31], which in turn contributes to the high mortality rate in sepsis-related syndromes [8]. For this reason, increasing the blood flow to the mesenteric circulation thus preventing the ischemia and organ injury [34] by means of endothelin receptor blockade was reported to be beneficial in animals [35] and in human beings [31].…”
Section: Discussionmentioning
confidence: 99%
“…rat model of endotoxemia. Oldner et al [28] on the other hand could not prove any beneficial effects of selective ET A antagonism on portal vein flow or ileal tonometry in endotoxemic pigs. Thus, the role of the different ET-1 receptor types in mediating microcirculatory dysfunction in the small intestine remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%